Revitalization of Theoretical Response Study of Ignaz Goldziher and Joseph Schacht Hadith Criticism - Moh Nawafil; Suparwany (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
Orientalist groups have been continuously investigating Islam and Muslim communities. One of their aspiring projects was to doubt the hadith of the Prophet Muhammad Peace be upon him through several divergences of its theoretical constructions. In responding to this case, the subject of hadith critique became an urgent tool to examine and maintain hadith authenticity. This library research analyzed descriptively several sources such as scientific articles, books, and research reports to answer the formulation of the problem. In this case, this article aims to identify the definition of hadith and its historical development, to disclose the brief orientalists' biographies discerned on inquiring the criticism of sanad through its theoretical framework. Finally, to respond to the hadits theoretical criticism by the orientalists. The findings in this paper were (1) Hadith criticism was regarded as a tool to distinguish the authenticity of hadith and determine the narrator's competency and disability; (2) Ignaz Goldziher conveyed his theoretical construction on the issue of hadith authenticity using a critical approach. While Goldziher introduced a projecting back theory to doubt the existence of hadith and transmission of sanad; (3), He ignored the tsiqah aspects of the narrators, history, reasoning, and comparisons with the Qur'an. What is more, Goldziher also made a deliberate change in matan. Hadith had existed during the Prophet Muhammad, and the Companions had used it to implement Islamic law, and the strict method of receiving and transmitting the sanad dismantled Schacht's projecting back theory.